Intermittency, backup and overcapacity in wind energy: evidence from european countries - Flora, Rui Manuel Calado (2015)
In this paper, overcapacity of wind energy is analyzed using panel data techniques for a set of 19 European countries for the span of time 1998-2009. We control for the effect of conventional energy sources, namely coal-based and gas-fired power plants. These energy sources are mainly used to backup electricity generation in windless periods and in peak-load times. The effect of other renewable energy sources is also assessed. Results suggest that wind power growth rate and population density raises overcapacity. We also test the total of energy measures taken in Europe under long term energy goals. We extend the debate of renewables intermittency, highlighting the overcapacity issue and suggesting possible solutions to smooth out this problem.